First molecular identification of Cryptosporidium species isolated from canal water bodies in Minya Al-Qamh district, Northern Egypt - Marwa Omar; Samia E. Etewa; Tahani I. Farag; Samar Abd EL-Nabi; Heba Abdelal (BMC Research Notes)
Abstract Objective This study aimed to assess the prevalence of Cryptosporidium genotypes in the canal water bodies of Minya Al-Qamh District in Sharqia Governorate, Northern Egypt. Rural populations in Egypt lack access to clean water. They obtain their water supplies from different drains and canals, which are frequently exposed to contamination by human activities and untreated agricultural waste, introducing Cryptosporidium infection to unprotected waterways. A total of (72) canal water samples served for the molecular detection of Cryptosporidium species by PCR amplification and sequencing. Results Only one sample 1.4% (1/72) belonging to the village of Al-Aziziyyah was PCR-positive for Cryptosporidium contamination. Based on the (COWP) gene sequencing, this species was identified as Cryptosporidium parvum (C. parvum). The current work’s findings marked the first report on the molecular characterization of Cryptosporidium species in the canal water of Sharqia Province. Our results suggested that the source of C. parvum contamination could be of human and/or animal origin. Therefore, further studies are warranted to track the source of human infection and mitigate contamination for improved water quality.